The plight of absent fathers caused by migrant work: Its traumatic impact on adolescent male children in Zimbabwe - Nyanjaya, Ananias K. (HTS teologiese studies, 2012)
This article revealed the degree of trauma experienced by male adolescents when their fathers are absent. The cost of this absence could not be balanced with the material benefits the children have enjoyed, for the benefits have been outweighed by the trauma that children experience in the absence of their fathers. The emotions and tears expressed during the research journey have revealed that material support cannot compensate for the love and presence children expect from their fathers. The deep hurt instilled in their hearts by the periods of absence angered them and led to traumatic experiences. The protracted period of living with only one primary caregiver has imprisoned them into the feminised environment, thereby robbing them of a male identity. Therefore, this article was devoted to creating a shepherding model of caring for boys whose fathers are absent.